Formation of nanocarrier systems by dense gas processing - Beh, C.; Mammucari, R.; Foster, Neil (American Chemical Society, 2014)
© 2014 American Chemical Society. (Chemical Equation Presented) Nanocarrier systems, such as liposomes, polymersomes, and micelles, find applications in the delivery of a wide range of compounds, including targeted delivery of pharmaceuticals. Nanocarrier systems have the ability to increase the bioavailability, reduce toxicity, and avoid undesirable interactions of active pharmaceutical ingredients. In this work, a novel dense gas technique known as depressurization of an expanded solution into aqueous media (DESAM) was used to produce different types of nanocarrier systems. The effects of using different types of dense gases and different operating temperatures were investigated. Encapsulation of hydrophilic compounds in the vesicles (liposomes and polymersomes) was also studied. The highest encapsulation efficiencies in liposomes and polymersomes achieved were 10.2 and 9.7%, respectively. The DESAM process was also able to reduce the residual solvent content in the product to 2.2% (v/v), which is significantly lower than the solvent residual levels reported for conventional processing.